2019
DOI: 10.1021/jacs.9b03101
|View full text |Cite
|
Sign up to set email alerts
|

Selective Copper Complex-Catalyzed Hydrodefluorination of Fluoroalkenes and Allyl Fluorides: A Tale of Two Mechanisms

Abstract: The transition to more economically friendly small-chain fluorinated groups is leading to a resurgence in the synthesis and reactivity of fluoroalkenes. One versatile method to obtain a variety of commercially relevant hydrofluoroalkenes involves the catalytic hydrodefluorination (HDF) of fluoroalkenes using silanes. In this work it is shown that copper hydride complexes of tertiary phosphorus ligands (L) can be tuned to achieve selective multiple HDF of fluoroalkenes. In one example, HDF of the hexafluoroprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 118 publications
0
24
0
Order By: Relevance
“…25c In a detailed experimental and theoretical mechanistic study, Baker, Ehm, and co-workers demonstrated that triphenylphosphine-copper hydride is an excellent catalyst for the hydrodefluorination of various fluoroalkenes using silanes. 29…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25c In a detailed experimental and theoretical mechanistic study, Baker, Ehm, and co-workers demonstrated that triphenylphosphine-copper hydride is an excellent catalyst for the hydrodefluorination of various fluoroalkenes using silanes. 29…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Skalenko and his co-workers developed a method for the synthesis of 3-azabicyclo[3.2.0]heptanes (29) from N-benzylmaleimide (28) and alkenes by [2+2] photocycloaddition (Scheme 3D). 17 The reactions take place in the presence of benzophenone as photosensitizer, mostly with moderate yields.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] Commonly, the C-F bond activation is promoted by the formation of stable bonds such as H-F, B-F, Si-F or Al-F bonds among others. [13][14][15][16][17][18] At rhodium, the complexes [Rh(E)(PEt 3 ) 3 ] (E ¼ H, F, boryl, silyl, germyl) exhibit distinct reaction pathways for the C-F or C-H bond activation of HFOs. [19][20][21][22][23][24][25] For example, the activation of 2,3,3,3-tetrauoropropene using [Rh(F)(PEt 3 ) 3 ] in the presence of uorosilane resulted in the C-H bond activation and a concomitant 1,2-uorine shi.…”
Section: Introductionmentioning
confidence: 99%
“…bond formation and precise retention of partially fluorinated scaffold, although most of the advances focus on the manipulation of single CÀ F bond. Compared with more activated aromatic [21][22][23][24][25] or vinylic analogues, [26][27][28][29][30][31][32][33] selective aliphatic C(sp 3 )À F functionalization of unreactive perfluoroalkyl substance with multiple CÀ F bonds attached remote to π-system is relatively uncommon. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] The successful realization of this challenging issue is complicated by several apparent factors (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%